Hyperprolactinaemia in a patient with kidney failure - Parak, Amirah; Daya, Reyna; Bulbulia, Saajidah; Seedat, Faheem; Bayat, Zaheer (African Journal of Nephrology, 2020)
Hyperprolactinaemia is a common endocrine abnormality in patients with kidney failure. A 43-year-old female, known with kidney failure on maintenance haemodialysis, was referred with symptomatic hyperprolactinaemia. Biochemical investigations revealed a markedly elevated serum prolactin level. Magnetic resonance imaging of the brain (without gadolinium) demonstrated a pituitary macroadenoma. The patient was started on cabergoline therapy. This case discusses hyperprolactinaemia in kidney failure and highlights the importance of investigating markedly elevated prolactin levels. In cases where patients have galactorrhoea, headaches and/or visual disturbances, clinicians should be alert to the possibility of a prolactin-secreting pituitary tumour.